Elevation of serum E-selectin in Thai hyperlipidemia adults - Michuea, Apinya; Fongsupa, Somsak; Rerksngarm, Thaval; Kongkhum, Sudawadee (International Journal of Research in Medical Sciences, 2021)
Background: Hyperlipidemia is an important risk factor of cardiovascular diseases (CVD), whose pathogenesis involves vascular endothelial dysfunction. Therefore, a specific marker of endothelial dysfunction, serum E-selectin, was assessed in Thai hyperlipidemia adults. Methods: Subjects who had no history of hypertension, diabetes and other serious illness were recruited and classified as normolipidemia (n=100) and hyperlipidemia (n=100), by using the levels of blood lipids (hyperlipidemia: total cholesterol >200 mg/dl, low density lipoprotein cholesterol (LDL-C) >130 mg/dl, and triglyceride >150 mg/dl). Clinical data were collected, and laboratory analysis was done. Serum levels of uric acid, fasting blood glucose (FBS), blood urea nitrogen (BUN), and creatinine were measured by the dry chemistry automate analyzer. Serum E-selectin was measured by using the enzyme-linked immunosorbent assay. Results: The hyperlipidemia subjects had significantly higher serum E-selectin levels than the normolipidemia subjects (18.98±11.58.56 versus 8.85±4.02 ng/ml). E-selectin was significantly correlated with blood lipids; total cholesterol, triglyceride, LDL-C, and HDL-C (r=0.477, 0.441, 0.453, and -0.191, respectively). Moreover, significant correlations of E-selectin with uric acid and fasting blood glucose were also found (r=0.155 and 0.166, respectively). Conclusions: Serum E-selectin levels increased in hyperlipidemia and correlated with uric acid and fasting blood glucose, reflecting the association between hyperlipidemia and pathogenesis of CVD, Therefore, it emphasizes the importance of hyperlipidemia management.